DEVELOPING AUTHENTIC E-LEARNING LISTENING MATERIALS OF NARRATIVE TEXT BASED ON LOCAL FOLKLORE FOR THE TENTH GRADE STUDENTS - Titania Ayu Dwisari; Anni Holila Pulungan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
The objective of this study was to develop authentic E-learning listening materials of narrative text based on local folklore for the tenth-grade students in SMA Plus Sedayu Nusantara. This study was conducted by using Research and Development design through six stages; gathering data and information, need analysis, materials development, validating by experts, revising, and final product. The subject of the study was the tenth-grade students in SMA Plus Sedayu Nusantara. The data were gathered by reviewing documents, conducting an interview with the English teacher, and distributing the students' needs analysis questionnaires to X MIA 4 consists of 27 students to get the students’ needs. The interview and questionnaire results proved that the students needed authentic E-learning listening materials based on local folklore. The developed reading materials were validated by two experts which scored 3.52 and 4.79 on average. The scores approved that the authentic E-learning listening materials based on local folklore were valid and very valid to use for the tenth-grade students in SMA Plus Sedayu Nusantara. The result of the product was distributed to the students through Blog.Key words: Development, E-learning, Listening Materials, Authentic Materials, Local Folklore, Blog.